Occurrence of vancomycin-resistant enterococci in chickens in Malaysia - Abdul Majid, Mohd Shah; Abd Rahim, Ana Maria; Safee, Shahidayani; Awang Masheri, Dayang Salwani; Bejo, Siti Khairani (British Veterinary Association, 2007)
Cloacal swabs from 1097 and 604 commercial and free range village chickens, respectively, were analysed to determine the occurrence of vancomycin-resistant enterococci (VRE). Results revealed that Enterococcus faecalis and E. faecium were the predominant vancomycin-resistant species isolated from commercial chickens. 83 samples of Enterococcus sp. isolated from the free range chickens were vancomycin resistant. It is suggested that the high rate of VRE in poultry is linked to the use of avoparcin as a feed additive in commercial farms.